Instagram as a virtual art display for medical students - Pippitt, Karly; Chow, Candace; Case, Gretchen (Canadian Medical Education Journal, 2021)
Implication Statement We require our medical students to create art as part of a core course. Projects have historically been displayed at our health sciences library. During a rapid adjustment to virtual teaching at the onset of the COVID-19 pandemic, using Instagram to hold a virtual art show was a quickly implemented alternative. With student consent, course directors posted different artwork every weekday for eight weeks to a course account. By capitalizing on the visual strengths and extensive reach of the Instagram platform, we promoted our medical students’ talents both locally and nationally. We plan to use Instagram and in-person displays in the future.